COLLABORATION ON DAS CITARUM HANDLING THROUGH THE TNI BHAKTI PROGRAM AND LAW ENFORCEMENT IN THE FRAMEWORK OF MILITARY CAMPAIGN STRATEGY - Andri Amijaya Kusumah; Surya Wiranto; Aris Sarjito; Priyanto Priyanto; Buddy Suseto; Lukman Yudho Prakoso (Jurnal Cakrawala Ilmiah, 2023)
The management of the Citarum Watershed (Watershed) carried out through collaboration between the TNI (Indonesian Armed Forced) through the Regional Military Command (Kodam) III/Siliwangi and the Regional Government has so far not shown significant results. For this reason, this study aims to analyze the collaboration in handling the Citarum Watershed through the Bhakti TNI and law enforcement, using a qualitative method. Where from the research conducted it was found that the implementation of the Collaboration Bhakti TNI Kodam III/Siliwangi in the handling of the Citarum Watershed and law enforcement is still faced with sectoral egoism with supporting factors in the form of regulations so that multi-sector synergy with related stakeholders is integrated. Efforts carried out in collaboration in handling the Citarum watershed and law enforcement require the participation of environmentally conscious communities on the Citarum Riverbanks and Standard Operating Procedures (SOP)/Status Procedures (Protap), Memorandum of Understanding (MoU), as well as Working Relations Mechanisms in cooperation in the arrangement of the Citarum Watershed . Collaboration in handling the Citarum watershed through Bhakti TNI and law enforcement in supporting military campaign strategies requires synergy, speed and accuracy in moving people, infrastructure and equipment, as well as unity of command. To realize this, it was suggested to the President to issue a Presidential Regulation regarding the involvement of the Regional Military Commander III/Siliwangi as the person in charge of the ecosystem and environment, the need for education to increase the participation of environmentally conscious communities on the Citarum River Basin, as well as the formulation of SOP or Protap including MoU between components in pentahelix , Mechanism of Working Relations in accelerating the arrangement of the Citarum Watershed.